Exploring community level multi-agency communication and collaboration during the emergency response to the covid-19 pandemic - Rachel K. Wilkinson; John G. Richmond (Elsevier, 2023)
Objectives: This study assesses multi-agency communication and collaboration during the community emergency response to the covid-19 pandemic. Study design: Qualitative case-study research. Methods: Semi-structured qualitative interviews were conducted with ten officers from organisations involved in the community response to the pandemic, at strategic or tactical level, within an English local authority (LA) area. Interviews were thematically analysed. Results: Horizontal (local/regional) communication and collaboration between the multi-agencies was found to be effective. Participants felt multi-agency groups had a sense of shared identity, partly from pre-existing relationships and a sense of shared common fate. The unified command model, with incident management co-chaired by the local authority, fire and police was found to support joint working, bolstering response effectiveness. There was frustration with vertical (national) communication and collaboration. Messages to local responders were often delivered via daily Government briefings to the public, meaning local responders had little time to consider and implement appropriate actions. Conclusions: The study provides new and impactful insights into the community response in an English MBC area during the Covid-19 pandemic. However, findings apply to any high-or-low-income country if their emergency planning/response considers community level integration with multiple-agencies to improve the public health emergency response. Set against existing international literature, show good command-and-control structures, including leadership, training and positive local culture were important for successful communication and collaboration between the multi-agencies. This study highlights some beneficial practices which support recovery and preparedness for future emergencies.